Розробка хімічного складу і режимів термічної обробки сталі для залізничних коліс з підвищеною стійкістю до зношування при високих навантаженнях на вісь - Бабаченко, О.І.; Кононенко, Г.А.; Подольський, Р.В.; Сафронова, О.А. (Physico-technological Institute of Metals and Alloys, 2024)
One of the directions of the development of railway transport is increasing the load on the axle, while it is necessary to create new, more wear-resistant materials to increase the durability of railway wheels. At the same time, in many cases, a high level of hardness and strength must be combined with no less high values of plasticity and viscosity indicators. Purpose: to investigate the effect of the developed chemical composition and processing modes on the mechanical properties of laboratory-produced steels for railway wheels with increased wear resistance, which work in light braking conditions with high axleloads. Material and methodology. Research was carried out on steels of the experimental composition of the laboratory manufacturing method. Metallographic studies of experimental and industrial steels were performed on a light microscope "Neophot 32" and "Axiovert 200 M MAT" of the company "Carl Zeiss". Grinds were made mechanically. The microstructure was revealed by etching in a 2—3 % alcoholic solution of nitric acid (HNO3). Mechanical tensile tests at room temperature were carried out according to standard methods. Results. Based on the results of analytical studies and calculation models that allow predicting the mechanical properties of steels depending on the content of chemical elements in the steel, the chemical composition of small-volume experimental ingots for smelting in laboratory conditions was developed. Smelting of experimental melts has been completed. The possibility of obtaining a full set of mechanical properties and microstructure, standardized by the requirements of AAR M-107/M-208 for railway wheels of class D from developed steel, has been established.